Effects of iron-containing minerals on hydrothermal reactions of ketones. (15th February 2018) - Yang, Ziming; Gould, Ian R.; Williams, Lynda B.; Hartnett, Hilairy E.; Shock, Everett L.
Abstract: Hydrothermal organic transformations occurring in geochemical processes are influenced by the surrounding environments including rocks and minerals. This work is focused on the effects of five common minerals on reactions of a model ketone substrate, dibenzylketone (DBK), in an experimental hydrothermal system. Ketones play a central role in many hydrothermal organic functional group transformations, such as those converting hydrocarbons to oxygenated compounds; however, how these minerals control the hydrothermal chemistry of ketones is poorly understood. Under the hydrothermal conditions of 300 °C and 70 MPa for up to 168 h, we observed that, while quartz (SiO2 ) and corundum (Al2 O3 ) had no detectable effect on the hydrothermal reactions of DBK, iron-containing minerals, such as hematite (Fe2 O3 ), magnetite (Fe3 O4 ), and troilite (synthetic FeS), accelerated the reaction of DBK by up to an order of magnitude. We observed that fragmentation products, such as toluene and bibenzyl, dominated in the presence of hematite or magnetite, while use of troilite gave primarily the reduction products, e.g., 1, 3-diphenyl-propane and 1, 3-diphenyl-2-propanol. The roles of the three iron minerals in these transformations were further explored by (1) control experiments with various mineral surface areas, (2) measuring H2 in hydrothermal solutions, and (3) determining hydrogen balance among the organic products. These results suggest the reactions catalyzed by iron oxides (hematite and magnetite) are promoted mainly by the mineral surfaces, whereas the sulfide mineral (troilite) facilitated the reduction of ketone in the reaction solution. Therefore, this work not only provides a useful chemical approach to study and uncover complicated hydrothermal organic-mineral interactions, but also fosters a mechanistic understanding of ketone reactions in the deep carbon cycle.